2016
DOI: 10.1037/cpb0000065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating fit in employee selection: Beliefs about how, when, and why.

Abstract: Research strongly supports the use of standardized assessment methods, like structured interviews, to evaluate applicants. Many practitioners, however, continue to prefer unstructured and intuition-based approaches to employee selection. Nonstandardized assessment methods compromise the reliability and predictive validity of employeeselection systems and expose the hiring process to the idiosyncratic beliefs and biases of decision makers. To better understand practitioners' beliefs about decision making for em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The science-practice gap may also be reduced by influencing the perceptions of other stakeholders like applicants and managers, as they seem to affect the adoption of evidencebased assessment practices (Diab et al, 2011;Nolan et al, 2016). This is important because these stakeholders may not be as well informed about evidence-based assessment as assessment professionals and hence do not feel a need for change (Lawler, 2007).…”
Section: Practical Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The science-practice gap may also be reduced by influencing the perceptions of other stakeholders like applicants and managers, as they seem to affect the adoption of evidencebased assessment practices (Diab et al, 2011;Nolan et al, 2016). This is important because these stakeholders may not be as well informed about evidence-based assessment as assessment professionals and hence do not feel a need for change (Lawler, 2007).…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…Assessment professionals and managers may also have different aims when selecting candidates. Nolan et al (2016) showed that practitioners who did not expect to work together with an applicant considered the fit between the applicant's ability and the job demands more important than the fit between the applicant's values and the organization's characteristics. In contrast, practitioners who expected to work together with an applicant considered the fit between the applicant's values and the organization's characteristics more important.…”
Section: Aims Of Assessment and Selectionmentioning
confidence: 99%
See 3 more Smart Citations